NGUSABA LAMPUAN TRADISI MASYARAKAT DESA BAYUNG GEDE (KAJIAN TEOLOGI SOSIAL) - I Putu Windu Mertha Sujana; I Wayan Titra Gunawijaya (Jnanasidanta, 2021)
Worshiping God can be carried out in various aspects through His manifestations, this form explains that God's position must not only be worshiped but there should be a reunification between human beings when implementing a Ngusaba Lampuan tradition. A qualitative approach is used in an effort to find information and a research approach as a scientific method which is then presented in the form of a qualitative description. The results of the study include the implementation of the Ngusaba Lampuan tradition which is more directed to the inner feelings of the community that have been satisfied, inner satisfaction or the level of one's religiosity is certainly different from the others. The inner satisfaction of the community also depends on the situation and conditions around it or it could be that the vibrations that arise from the rituals, prayers and sincerity offered are the best according to the devotee, so that in the implementation of the ngusaba Lampuan tradition, more emphasis is placed on how to interpret symbols such as the value of religious communication seen from the sincere white chicken. as a symbolic substitute for the ceremonial fertilizer, prayers that do not use flowers and are reflected in all ceremonial ritual activities do not use puja/mantra but how the person interprets and does it with a sincere sense of sincerity. Keyword: Ngusaba Lampuan, Teologi Sosial